Enhancing Adolescents' Self-Esteem Through Rational Emotive Behavior Counseling: A Pre-Experimental Study in Junior High School Students - Widyarto, Wikan Galuh; Ramli, M; Machfud, Muchammad Saiful; Mramra, P. V. I. Pratiwi (Buletin Konseling Inovatif, 2025)
The aim of this study is to find out the level of self-esteem of students and how effective rational emotive behavioral counselling is to increase self-esteem. Quantitative research using pre-experiment, one group pretest posttest design. The study involved 32 students as a population, with 5 students who had low self-esteem as a sample. Purposive sampling method is used to obtain samples. The results show the self-esteem level of State Middle School 1 students Sumbergempol is in the lowest category of 10 (31%), medium 16 (50%), and high 6 (19%). There was a significant difference between the results before and after treatment with rational emotive behavioral counselling, according to the t-test double sample test, with a 2-tailed Sig significance value of 0.001 <0.05, which means there were significant differences between the outcomes prior and following treatment, so that rational emotive behavior counseling effectively increased the student's self-esteem. Rational Emotive Behavior Counseling (REBC) is effective in improving self-esteem because this approach focuses on cognitive restructuring, which involves changing irrational beliefs that contribute to low self-esteem into more rational and adaptive thought patterns. Additionally, REBC teaches emotional regulation and behavior management skills, helping individuals develop a more positive self-perception, increase self-confidence, and build resilience against social and emotional pressures.